Photorelease of tryptophan and its 5-hydroxy derivative from the corresponding pyrenyl cages - Fernandes, Maria José G. (2012)
L-Tryptophan, an essential amino acid is known to play important biological roles, most of them being associated to metabolic pathways involved in tryptophan catabolism. It is the precursor for the synthesis of serotonin, an important neuromediator associated to mood, stress response, sleep and appetite regulation. L-Tryptophan has numerous applications, it can be converted to hormones, such as 5-hydroxy tryptophan which has the function of antidepressant, relieving nervous tension, and improving sleep [1]. The technique of liberating biologically active compounds from photolabile precursors, under irradiation with UV light is a valuable tool for studies of biological processes since allows the temporal and spatial control of the activity of biological effectors [2]. Following our research interests, that include the synthesis and photocleavage of fluorescent bioconjugates of neurotransmitters amino acids [3], in this communication we report the synthesis of fluorescent pyrenyl bioconjugates of tryptophan 1a,b and 5-hydroxytryptophan 1c,d, and a study of their behaviour in different photocleavage conditions, namely the wavelength of irradiation, in a photochemical reactor equipped with lamps of 254, 300, 350 and 419 nm.